Le rêve inachevé d’étudier et de socialiser en français en toute sécurité linguistique : les perspectives d’étudiants franco-ontariens - Jean-Pierre, Johanne (Canadian Journal of Higher Education, 2017)
Using an interpretative approach, this paper examines the perspectives of Franco-Ontarian postsecondary students employing an exploratory qualitative research. Between January and June 2014, in-depth semi-structured interviews were conducted in Ottawa and Toronto with 18 Franco-Ontarian postsecondary students. The findings reveal that participants who study in bilingual postsecondary institutions would like to have access to courses in French, as well as see improvement in the quality of the language of instruction, and the opportunities to socialize in French. Participants who study in French-language postsecondary institutions express satisfaction with their learning experience, whereas participants who study in English-language postsecondary institutions express sentiments of linguistic isolation. In addition, the lack of socialization opportunities in French and the underrepresentation of Franco-Ontarian realities in the curriculum combined with instances of linguistic intimidation fuel linguistic insecurity.